2015
DOI: 10.15761/crt.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Estriol review: Clinical applications and potential biomedical importance

Abstract: The clinical relevance and biological significance of estriol (E3), one of the three major human estrogens, are presented in this review. While initially having limited therapeutic indications, research has demonstrated E3's utility as a biomarker to screen for disease, to test for placental function, and as a novel drug for human use. Current research is further exploring E3's potential as a diagnostic and therapeutic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
1
20
1
Order By: Relevance
“…[ 45 49 ]). While estrone and estriol are less bioactive than estradiol, their effects on dendritic spines require future investigation, especially with regards to pregnancy (when circulating estriol levels increase greatly as a result of placental production [ 50 ]) and post-menopause (when 17β-estradiol levels decline more so than estrone levels leading to estrone becoming the most abundant of the estrogens [ 51 ]), periods in which hippocampal dendritic spine numbers are increased [ 52 , 53 ] and decreased (typically investigated via ovariectomy) [ 32 , 54 56 ], respectively. It should further be mentioned that this review does not cover the effects of phytoestrogens (weak estrogens found in plants) or endocrine disruptors such as bisphenol-A on dendritic spine density or neurogenesis; however, there is emerging evidence that phytoestrogens may affect these types of hippocampal plasticity [ 57 – 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 45 49 ]). While estrone and estriol are less bioactive than estradiol, their effects on dendritic spines require future investigation, especially with regards to pregnancy (when circulating estriol levels increase greatly as a result of placental production [ 50 ]) and post-menopause (when 17β-estradiol levels decline more so than estrone levels leading to estrone becoming the most abundant of the estrogens [ 51 ]), periods in which hippocampal dendritic spine numbers are increased [ 52 , 53 ] and decreased (typically investigated via ovariectomy) [ 32 , 54 56 ], respectively. It should further be mentioned that this review does not cover the effects of phytoestrogens (weak estrogens found in plants) or endocrine disruptors such as bisphenol-A on dendritic spine density or neurogenesis; however, there is emerging evidence that phytoestrogens may affect these types of hippocampal plasticity [ 57 – 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estriol inhibits the bond between estradiol and estrogen receptors (35). In an in vitro environment, estriol is known as an insulin resistance factor (26). Consequently, increased estriol in pregnancy could likely be associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, estriol is a weak estrogen agonist that has a strong antagonistic activity along with estradiol (25). Unconjugated Estriol (UE) has led to insulin resistance under in vitro conditions (26). Moreover, the low levels of maternal serum UE in the second trimester have been associated with adverse pregnancy complications (27).…”
Section: Introductionmentioning
confidence: 99%
“…P4 and oestrogens are progressively secreted throughout gestation, and P4 levels are responsible for the maintenance of pregnancy [ 1 ]. Oestrogens, such as estriol (E3) and estrone sulphate (E1SO4), are produced by the placenta from dehydroepiandrosterone sulphate (DHEA-S), which is synthesised exclusively by the foetal adrenal glands [ 4 ]. E1SO4 acts as a reserve for the peripheral formation of bioactive estrogenic forms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…E1SO4 acts as a reserve for the peripheral formation of bioactive estrogenic forms [ 5 ]. Likewise, E3 is the dominant oestrogen hormone during pregnancy and is used as an index of the state of the foetal-placental unit since its production depends on the synthesis capacity of the foetus and placenta together [ 4 ]. C levels are associated with the placental synthesis of crucial oestrogens for the maintenance of pregnancy, [ 5 ] playing an important role throughout pregnancy, and are responsible for maintaining intrauterine homeostasis.…”
Section: Introductionmentioning
confidence: 99%